A BNCC e os dilemas da diversidade no Brasil contemporâneo : reflexão docente na construção de uma aprendizagem antirracista no ensino de História - Varella, Nayara Bianca Serra (2021)
The main theme of the present work is the National Common Curricular Base (BNCC), Curriculum and the context of an antiracist education for the teaching of History. In this sense, the general objective is to analyze the Base document with emphasis on its first version focused on elementary education final years, and to promote antiracist learning situations for the teaching of History. Assuming that the BNCC is an official document that is aligned with a political project, presenting an intentionality and a social place of production, the methodology for this theme goes through analyzes of the legislation in force and speeches made available in the media, and articles specialized in that highlight the power relations inherent in its construction, identifying active groups, and the potential for advances when establishing, in its first version, an educational policy that benefits the basic skills for contemporary times. In this context, the motivation for the antiracist theme, when dealing with a real, difficult and urgent problem that affects our daily lives, aims to encompass the protagonism of the student, dialoguing with his experiences and his places of speech, expanding and articulating with reality student's social status, making learning more meaningful and accessible, thus breaking with a “traditional story”. Thus, when working with concepts related to the context of the world in the 19th century: racism, addressing through the use of the special Falas Negras, black protagonism from the perspective of the struggle and resistance to the fight against racism and inequalities, problematizing issues for debates and reflections, and video production in the classroom, the suggestion presented here permeates actions aimed at antiracist education in practice, by proposing situations of education for the positive strengthening of racial diversity, developing means that promote the construction of the selfconcept of students belonging to discriminated minorities.